Empire and the literature of sensation : an anthology of nineteenth-century popular fiction - Alemán, Jesse, 1968-; Streeby, Shelley, 1963- (Multi-ethnic literatures of the Americas., 2007)
Mid-nineteenth-century American literature teems with the energy and excitement characteristic of the nation?s era of expansion. It also reveals the intense anxiety and conflict of a country struggling with what it will mean, socially and culturally, to incorporate previously held Spanish territories. Empire and the Literature of Sensation is a critical anthology of some of the most popular and sensational writings published before the Civil War. It is a collection of transvestite adventures, forbidden love, class conflict, and terrifying encounters with racial?others.?. Most of the accounts,